KAJIAN MENGENAI PENGGUNAAN E-LEARNING DI KALANGAN MAHASISWA PERGURUAN TINGGI SWASTA DI KOTA PALEMBANG - Nasir, Muhammad; Kurniawan, Kurniawan (Universitas Bina Darma, 2015)
E-learning is a medium of learning delivered through the online. The media is often known as a Learning Management System system that can establish communication between faculty and students in the learning process. Most institutions, use of technology in the learning process which supports activities of college is a valuable asset. College success is usually to understand the advantages and usefulness of information technology, especially e-learning instructional media to support the colleges performance. This study contains a review of the behavior of the user to use the medium of e-learning in the learning process. This study uses a model framework that adopts the model UTAUT. Based on the obtained regression equation Y = 3.425 to 0.025 X1 + 0.025 X2 + 0.139 X3,iIn fact that the variable performance expectancy, effort expectancy does not affect the acceptance of e-learning learning using partially. But the influence of social variables affect the acceptance of e-learning learning using partially.